Micron-scale flake silver powder for HJT solar cell and preparation method thereof

By adding fatty acids as dispersant to the silver carbonate reduction reaction system and controlling the morphology and particle size of the silver powder by ball milling method, the problems of large specific surface area and high impurity content in the prior art were solved, and micron-scale flaky silver powder suitable for HJT solar cells were prepared.

CN119525482AActive Publication Date: 2025-02-28CSSC HUANGGANG PRECIOUS METALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411461674.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-28
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The silver powder prepared in the prior art has a large specific surface area and is prone to introduce more impurities, which cannot meet the requirements of silver powder for HJT solar cells.

Method used

The silver nitrate solution and sodium carbonate solution were used to react to obtain a solution containing silver carbonate, which was added dropwise to a mixed solution of reducing agent and fatty acid for reaction, and silver powder granules were obtained after washing and drying. Then, the silver powder particles, abrasive agent and organic solvent were mixed evenly, and ball milled, and separated, washed, dried, crushed and sieved to obtain micron-scale flake silver powder for HJT solar cells.

Benefits of technology

The prepared flake silver powder has the characteristics of high degree of flakeification, good dispersion, low specific surface area and high purity. It is suitable for the production of low-temperature conductive silver paste for HJT solar cells, and solves the problems of stable control of silver powder particle size, impurity elimination and surface modification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119525482A_ABST
    Figure CN119525482A_ABST
Patent Text Reader

Abstract

The invention relates to micron-sized flaky silver powder for an HJT solar cell and a preparation method of the micron-sized flaky silver powder, and the preparation method comprises the following steps: S1, reacting a silver nitrate solution with a sodium carbonate solution to obtain a solution containing silver carbonate, dropwise adding the solution containing silver carbonate into a mixed solution of a reducing agent and fatty acid for reaction, and washing and drying to obtain silver powder particles; s2, uniformly mixing the silver powder particles, a grinding aid and an organic solvent to obtain slurry; and S3, carrying out ball milling on the slurry, separating, washing, drying, crushing and sieving to obtain the micron-sized flake silver powder for the HJT solar cell. According to the preparation method, the morphology, the particle size and the impurity content of the flaky silver powder are effectively controlled, and the prepared flaky silver powder has the beneficial effects of being high in flaky degree, good in dispersity, low in specific surface area, high in purity and the like; the method is simple to operate and suitable for large-scale rapid production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of precious metal powders, and in particular relates to micron-level flaky silver powder for HJT solar cells and a preparation method thereof. Background Art

[0002] Low-temperature conductive silver paste and its functional material flaky silver powder have broad application prospects in the photovoltaic and electronics industries. As an important conductive functional material in low-temperature conductive silver paste, the physical and chemical properties of flaky silver powder, such as specific surface area, tap compaction, flake diameter and thickness, dispersibility and impurity content, have a great influence on the conductive properties of low-temperature conductive paste.

[0003] HJT (Heterojunction with Intrinsic Thin-layer, crystalline silicon heterojunction, abbreviated as HJT) solar cells have many advantages such as high conversion efficiency, low temperature coefficient, double-sided power generation, and low process temperature. The low-temperature conductive silver paste it uses uses silver powder as the main raw material, and has high requirements on the sheet diameter, dispersion and impurity content of the silver powder.

[0004] At present, the commonly used methods for preparing flaky silver powder at home and abroad are mainly chemical method and mechanical ball milling method. The chemical method can be further divided into liquid phase reduction method, template method, photoinduction method, microwave radiation method, etc. In the liquid phase reduction method, how to avoid excessive organic residues while improving dispersibility, resulting in reduced product conductivity, poor process stability and low yield. The flaky silver powder prepared by mechanical ball milling has bright color, large specific surface area and good conductivity, but the silver powder with too large specific surface area absorbs a large amount of oil, resulting in high viscosity and poor fluidity of the subsequent silver paste system, which affects the subsequent printing and feeding; and in order to improve the dispersibility of silver powder, the silver powder is usually surface modified, and a variety of dispersants or even emulsifiers are added, which makes post-processing difficult and the impurity content of the obtained silver powder is high; therefore, there are currently problems such as stable control of the particle size of silver powder for HJT solar cells, elimination of impurities, and surface modification. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a micron-sized flaky silver powder for HJT solar cells and a preparation method thereof, and solve the technical problem that the silver powder prepared in the prior art has a large specific surface area and is prone to introduce more impurities, and cannot meet the requirements of silver powder for HJT solar cells.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing micron-sized flaky silver powder for HJT solar cells, comprising the following steps: S1, reacting a silver nitrate solution and a sodium carbonate solution to obtain a solution containing silver carbonate, dropping the solution containing silver carbonate into a mixed solution of a reducing agent and a fatty acid for reaction, and obtaining silver powder particles through washing and drying; S2, uniformly mixing the silver powder particles, a grinding aid and an organic solvent to obtain a slurry; S3, ball-milling the slurry, and then separating, washing, drying, crushing and sieving to obtain micron-sized flaky silver powder for HJT solar cells.

[0007] In a second aspect, the present invention provides a micron-sized flaky silver powder for HJT solar cells prepared by the above-mentioned preparation method.

[0008] Compared with the prior art, the beneficial effects of the present invention include: In the preparation method of the present invention, by adding fatty acid as a dispersant in the silver carbonate reduction reaction system, the obtained silver powder particles are made uniform, which is conducive to improving the performance of the finally obtained flaky silver powder, and then the silver powder particles are used as raw materials, and ball milling is performed by using external mechanical force, grinding aids and organic solvents to effectively control the morphology, particle size and impurity content of the flaky silver powder. The prepared flaky silver powder has the characteristics of high degree of lamellarization, good dispersibility, low specific surface area, high purity, etc. The method is simple to operate, has good continuity in the processing process, large production batch, high reaction efficiency, and is suitable for large-scale rapid production. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a scanning electron microscope image of the flaky silver powder prepared in Example 1; Figure 2 This is a scanning electron microscope image of the flaky silver powder prepared in Example 2. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] The low-temperature conductive silver paste used in HJT solar cells uses silver powder as the main raw material, and has high requirements for the flake diameter, dispersibility and impurity content of the silver powder. The existing silver powder preparation is mainly based on chemical method and mechanical ball milling method. In the liquid phase reduction method, how to avoid excessive organic residue while improving dispersibility, resulting in reduced product conductivity, poor process stability and low yield. The flaky silver powder prepared by mechanical ball milling has bright color, large specific surface area and good conductivity, but the silver powder with large specific surface area absorbs a large amount of oil, resulting in high viscosity and poor fluidity of the subsequent silver paste system, which affects the subsequent printing and feeding. Therefore, there are currently problems such as stable control of silver powder particle size, elimination of impurities, and surface modification in the low-temperature conductive silver paste used in HJT solar cells, which makes its morphology difficult to control, the impurity content is high, and it cannot be mass-produced.

[0012] The present invention provides a micron-sized flaky silver powder for HJT solar cells and a preparation method thereof, thereby effectively solving the technical problems of mass production, morphology control, particle size control and high impurity level of flaky silver powder. The flaky silver powder prepared by the present invention can stably have a size of 1μm to 6μm, and is suitable for the production of low-temperature silver paste for HJT solar cells.

[0013] In addition, there are many forms of oxidants for preparing silver powder by liquid phase chemical reduction method, and the common ones are silver nitrate, silver carbonate, silver oxide, silver ammonium ion, silver halide, etc. The order of ionization degree of silver salt intermediates is: silver iodide < silver bromide (equivalent to silver sulfide) < silver ammonium ion < silver chloride < silver oxide < silver carbonate. The powder prepared by silver nitrate and ascorbic acid (VC) exhibits the characteristics of narrow particle size distribution, high sphericity, smooth surface, high tap density, etc. The flaky silver powder prepared by horizontal mechanical ball milling as the initial silver powder exhibits too regular flaky powder morphology and good uniformity. The application process often has defects such as high viscosity, poor thixotropy, and wire drawing. Therefore, the present invention mainly selects silver carbonate with the highest ionization degree as the silver source to prepare flocculent spherical initial silver powder, which can better solve the above problems.

[0014] In a first aspect, the present invention provides a method for preparing micron-sized flaky silver powder for HJT solar cells, comprising the following steps: S1, using a silver nitrate solution and a sodium carbonate solution to react to obtain a solution containing silver carbonate, adding the solution containing silver carbonate dropwise to a mixed solution of a reducing agent and a fatty acid to react, and washing and drying to obtain silver powder particles; S2, mixing the silver powder particles, the grinding aid and the organic solvent uniformly to obtain a slurry; S3, ball-milling the slurry, and then separating, washing, drying, crushing and sieving to obtain micron-sized flaky silver powder for HJT solar cells.

[0015] Preferably, in step S1, the molar ratio of silver nitrate to sodium carbonate is 1:(0.48-0.50); ​​the molar mass ratio of silver nitrate, reducing agent and fatty acid is 1:(0.60-0.62):(0.003-0.006).

[0016] Preferably, in step S1, the fatty acid includes one or more of lauric acid, myristic acid, oleic acid, palmitic acid and stearic acid; and the reducing agent includes ascorbic acid.

[0017] Preferably, in step S1, the concentration of the silver nitrate solution is 120-160 g / L; the concentration of the sodium carbonate solution is 35-50 g / L; the mixed solution of the reducing agent and the fatty acid is obtained by mixing the reducing agent solution and the fatty acid solution, wherein the concentration of the reducing agent solution is 35-50 g / L, and the concentration of the fatty acid is 48-55 g / L.

[0018] Preferably, in step S1, washing is performed with distilled water and anhydrous ethanol respectively. The present invention further reduces the content of organic matter through water washing and alcohol washing, and avoids excessive retention of dispersant, thereby affecting the impurity content of subsequent flaky silver powder.

[0019] Preferably, in step S1, drying is performed at 80-90° C. for 10-14 hours.

[0020] Preferably, in step S1, the average particle size of the silver powder particles is 0.8 μm to 1.0 μm.

[0021] Preferably, in step S2, the grinding aid includes oleic acid; and the organic solvent includes anhydrous ethanol or acetone.

[0022] Preferably, in step S2, the mass ratio of the silver powder particles, the grinding aid and the organic solvent is 100: (0.75-1.5): (45-55).

[0023] In the present invention, by adopting a relatively high amount of grinding aid and organic solvent, it is ensured that the outer surface of the silver powder particles is fully adsorbed and wrapped with an organic shell layer, thereby avoiding the occurrence of undesirable phenomena such as cold welding, agglomeration, and agglomeration in the subsequent ball milling process, which leads to undesirable phenomena such as a wide powder particle size distribution, a large D100, and a low first-time qualified rate.

[0024] Preferably, in step S2, after the silver powder particles, the grinding aid and the organic solvent are mixed, they are stirred for 5 min to 40 min using a high-speed disperser with a rotation speed of 800 to 1200 r / min to obtain a slurry.

[0025] Preferably, in step S3, the process conditions used for ball milling are: the diameter of the zirconia balls is 1.5-2.5 mm, the ball-to-material ratio is (2.8-3.2):1, the ball milling temperature is 35-42°C, the ball milling speed is 40-60 r / min, and the ball milling time is 5-10 h.

[0026] At the same time, compared with the defects of wall sticking or long ball milling time caused by using other substances as dispersants, for example, using ricinoleic acid as a dispersant will cause wall sticking, and using benzophenone oxime acetic acid benzophenone oxime ester ethanol solution as a dispersant has the defect of slow infiltration rate, and it is necessary to firstly ball mill at a low speed (30r / min) for 120min in the early stage of ball milling, and then increase the speed to 60r / min for formal ball milling; the present application uses oleic acid as a grinding aid, increases its dosage, and increases the dosage of organic solvent during ball milling, so that a slurry can be obtained by high-speed dispersion, and then high-speed ball milling is performed without wall sticking, and the desired target product can be obtained quickly, the ball milling time is short, the ball milling efficiency is effectively improved, and the specific surface area of ​​the obtained silver powder is low; it is more economical and environmentally friendly, and the organic dispersant used can be easily removed by post-treatment to obtain flaky silver powder with higher purity.

[0027] Preferably, in step S3, separation is performed by using a sieve to separate the slurry and zirconia balls after ball milling to obtain slurry A, and the zirconia balls are washed to obtain slurry B; slurry A and slurry B are combined and then vacuum filtered to obtain flaky silver powder; washing is performed by using deionized water to wash the flaky silver powder until the conductivity is ≤20μS / cm.

[0028] Preferably, in step S3, the drying is carried out at 50° C. to 80° C. for 8 h to 24 h; and the sieving is carried out using a 200-mesh sieve.

[0029] In a second aspect, the present invention provides a micron-sized flaky silver powder for HJT solar cells prepared by the above-mentioned preparation method.

[0030] Preferably, the diameter D50 of the micron-sized flaky silver powder for HJT solar cells is 1 to 6 μm, more preferably 2 to 4 μm; the bulk density is 2.75 to 3.6 g / cm 3 , tap density is 4.5~5.5g / cm 3 , the specific surface area is 0.33~0.52m 2 / g.

[0031] The main mechanism of action and advantages of the present invention: The present invention uses silver carbonate with the highest ionization degree as a silver source to prepare flocculent spherical ultrafine initial silver powder particles, and in the preparation process, adds a long straight-chain fatty acid as a dispersant, which has a moderate molecular weight and a high shrinkage rate during low-temperature solidification, especially lauric acid and oleic acid, so that the silver powder can grow evenly during the growth process, which is beneficial to improving the performance of the final flaky silver powder; and then uses ultrafine spherical silver powder particles as raw materials, and through the use of external mechanical force, with the help of grinding balls and grinding aids, through the frequent collision, friction, and extrusion between grinding balls, ball mills and spherical silver powder particles, the hammer forging, ball milling, and refinement of the material are achieved. Finally, the surface morphology and particle size distribution of the silver powder particles are all changed under the ball milling effect of a relatively short time, forming a product that meets the expected technical indicators. The present invention is through the processes of spherical silver powder particle preparation, dispersion, ball milling, washing and filtering, drying and crushing, etc., in the dispersion process, an organic solvent is added as a ball milling medium, and a grinding aid is added, and according to a certain ball-to-material ratio, the target flaky silver powder is prepared by a mechanical horizontal ball milling method.

[0032] The flaky silver powder prepared by the invention has the characteristics of high degree of flaking, good dispersibility, low specific surface area, high purity, etc. The flaky silver powder is used to prepare low-temperature conductive silver paste, which is beneficial to improving the fluidity of the silver paste. The flaky silver powder has high bulk density and tap density. The conductive film obtained after slurry adjustment and sintering has few and small voids, which is beneficial to improving the conductivity.

[0033] The present invention is further described in detail below through specific examples.

[0034] Example 1 A method for preparing micron-sized flaky silver powder for HJT solar cells comprises the following steps: S1, add 10.5kg (61.8mol) of silver nitrate to 75kg of distilled water to prepare a silver nitrate solution; add 3.2kg (30.2mol) of sodium carbonate to 75kg of water to prepare a sodium carbonate solution; add 6.6kg (37.5mol) of ascorbic acid to 150kg of distilled water to prepare a reducing agent solution; add 64g (0.32mol) of lauric acid to 1.25kg of distilled water to prepare a fatty acid solution, and mix the fatty acid with the reducing agent solution to obtain a mixed solution; A silver nitrate solution and a sodium carbonate solution are mixed and reacted to obtain a solution containing silver carbonate, and the solution containing silver carbonate is added dropwise to a mixed solution of ascorbic acid and lauric acid while stirring until the reaction is terminated. The product generated by the reaction is washed three times with distilled water and anhydrous ethanol respectively, and then dried at 85° C. for 12 hours to obtain silver powder particles.

[0035] S2, basic silver powder dispersion: 15 kg of silver powder particles, 120 g of oleic acid and 7.5 kg of anhydrous ethanol are mixed by a high-speed disperser at a stirring speed of 1000 r / min for 30 min to obtain a mixed slurry; S3, transfer the slurry to the ball mill for ball milling, add 45 kg of 2 mm diameter zirconia balls (i.e., the ball-to-material ratio is 3:1) into the horizontal ball mill, turn on the gas source, make the ball mill in a horizontal position, set the ball mill speed to 50 r / min, turn on the cooling system, maintain the system temperature at 40 °C for mixing and ball milling, and take samples for testing regularly.

[0036] When the technical index of the flake powder obtained by ball milling for 6 hours reaches the standard, the ball milling is stopped, and the silver powder slurry and the zirconium oxide balls are separated through a sieve, and the zirconium oxide balls are cleaned to obtain the slurry of the flaky silver powder. The flaky silver powder slurry is poured into the polyester filter bag of the stainless steel filter, and the solid-liquid separation is carried out by vacuum filtration to obtain the flaky silver powder; the silver powder in the filter bag is washed with deionized water several times until the conductivity is ≤20μS / cm.

[0037] The flaky silver powder was dried at 65° C. for 12 h in an electric blast drying oven to obtain a dry silver block. The dried flaky silver powder was crushed by a mixer and all of them were sieved through a 200-mesh sieve to obtain micron-grade flaky silver powder for HJT solar cells.

[0038] Example 2 The difference from Example 1 is that the sample is taken after ball milling for 10 hours, and the sample is obtained by washing, filtering and drying. The other steps and conditions are the same as those in Example 1.

[0039] Performance Testing 1 g of the prepared silver powder sample was ultrasonically dispersed in 50 mL of anhydrous ethanol for 5 min, and the particle size and distribution of the powder were tested by a particle size analyzer. The particle morphology and size were observed by a scanning electron microscope, the tap density and bulk density of the powder were measured by a tap density tester, the moisture and ash content of the powder were measured by a fully automatic moisture ash analyzer, and the specific surface area of ​​the powder was measured by a specific surface analyzer.

[0040] Scanning electron microscope observation revealed that the silver powder particles obtained in step S1 of Example 1 were spherical silver powders with an average particle size of 0.8 μm to 1.0 μm.

[0041] The results of the flake properties test at different ball milling times in Examples 1 and 2 are shown in Table 1 below.

[0042] Table 1 Flake performance test results of different ball milling times in Examples 1 to 2

[0043] From the data in Table 1 above, it can be seen that the process of the present invention can be used to prepare flaky silver powder in the range of 1 μm-6 μm. Example 1 The average D50 of the flaky silver powder is 2.0 μm, and the tap density is 5.5 g / cm 3Example 2: The average D50 of the flaky silver powder is 4.0 μm, and the tap density is 6.0 g / cm 3 The prepared flaky silver powder has the characteristics of high degree of flaking, good dispersibility, low specific surface area (low oil absorption, the viscosity of the slurry system is not too high, and does not affect the subsequent printing and fluidity, etc.), high tap density, high purity, etc., and is very suitable for low-temperature slurry for HJT solar cells.

[0044] Depend on Figure 1 and Figure 2 It can be seen that the micron-sized flaky silver powder for HJT solar cells prepared in Examples 1 and 2 of the present invention is evenly distributed, and from Table 1 and Figure 1-Figure 2 It can be seen that as the ball milling time increases, the flake diameter of the obtained flaky silver powder will increase and the specific surface area will increase. If the specific surface area increases further, it will affect subsequent use; therefore, the preferred ball milling time of the present invention is 5 to 10 hours.

[0045] According to the X-ray diffraction test, the micron-sized flaky silver powder for HJT solar cells prepared in Examples 1 and 2 of the present invention has no impurity diffraction peaks, indicating that it has high purity.

[0046] Comparative Example 1 The difference from Example 1 is that the amount of the dispersant lauric acid in step S1 is 0 (ie, the dispersant is removed); the other steps and conditions are the same as those in Example 1.

[0047] The results showed that the obtained silver powder particles agglomerated, resulting in a wide particle size distribution of the final flaky silver powder, an increase in specific surface area, and a decrease in yield.

[0048] Comparative Example 2 The difference from Example 1 is that the amount of anhydrous ethanol in step S2 is adjusted to 6 kg; the other steps and conditions are the same as those in Example 1.

[0049] As a result, it was found that the specific surface area of ​​the obtained flaky silver powder was increased.

[0050] Comparative Example 3 The difference from Example 1 is that the oleic acid in step S3 is adjusted to benzophenone oxime acetic acid benzophenone oxime ester; the other steps and conditions are the same as those in Example 1.

[0051] The results showed that the powder adhered to the wall, the yield was reduced, and the purity of the obtained flaky silver powder was reduced, indicating that it was difficult to remove by washing.

[0052] From the comparison of Examples 1-2 and Comparative Examples 1-3, it can be seen that the present invention adds a long straight-chain fatty acid as a dispersant during the preparation of silver powder particles, so that the prepared silver powder particles are uniform, which is beneficial to improving the performance of the finally obtained flaky silver powder; then the silver powder particles are used as raw materials, and high-speed ball milling is performed with the help of external mechanical force, a relatively high amount of grinding aids and organic solvents, without wall sticking phenomenon, short ball milling time, and effectively improving ball milling efficiency. The obtained flaky silver powder has a uniform and moderate flake diameter, a small specific surface area, a high purity, and a large loose density and a tap density.

[0053] The present invention provides a micron-sized flaky silver powder for HJT solar cells and a preparation method thereof. The ultrafine spherical silver powder particles obtained by reducing with a reducing agent are used as raw materials, and organic solvents and organic grinding aids are added. The target product is obtained by mechanical ball milling, filtering, washing and drying. The present invention solves the technical problems of inconsistent particle size and morphology, high impurity content and surface modification required in the traditional flaky silver powder preparation process. The average particle size of the obtained flaky silver powder is stable at 1μm to 6μm, the operation is simple, and batch production is possible. It is particularly suitable for the production needs of silver powder for low-temperature silver paste.

[0054] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing micron-sized flaky silver powder for HJT solar cells, characterized in that: The following steps are involved: S1, using a silver nitrate solution and a sodium carbonate solution to react to obtain a solution containing silver carbonate, adding the solution containing silver carbonate dropwise to a mixed solution of a reducing agent and a fatty acid to react, and washing and drying to obtain silver powder particles; S2, mixing the silver powder particles, the grinding aid and the organic solvent uniformly to obtain a slurry; S3, ball-milling the slurry, and then separating, washing, drying, crushing and sieving to obtain micron-sized flaky silver powder for HJT solar cells.

2. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: The following steps are involved: In step S1, the fatty acid includes one or more of lauric acid, myristic acid, oleic acid, palmitic acid and stearic acid; and the reducing agent includes ascorbic acid.

3. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: In step S1, the molar ratio of silver nitrate to sodium carbonate is 1:(0.48-0.50); ​​the molar mass ratio of silver nitrate, reducing agent and fatty acid is 1:(0.60-0.62):(0.003-0.006).

4. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 3, characterized in that: In step S1, the concentration of the silver nitrate solution is 120-160 g / L; the concentration of the sodium carbonate solution is 35-50 g / L; the mixed solution of the reducing agent and the fatty acid is obtained by mixing the reducing agent solution and the fatty acid solution, wherein the concentration of the reducing agent solution is 35-50 g / L, and the concentration of the fatty acid is 48-55 g / L.

5. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: In step S1, washing is performed with distilled water and anhydrous ethanol respectively; Drying is done at 80-90°C for 10-14h; The average particle size of the silver powder particles is 0.8 μm to 1.0 μm.

6. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: In step S2, the grinding aid includes oleic acid; the organic solvent includes anhydrous ethanol or acetone; The mass ratio of silver powder particles, grinding aid and organic solvent is 100: (0.75-1.5): (45-55).

7. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: In step S2, the silver powder particles, the grinding aid and the organic solvent are mixed and stirred for 5 to 40 minutes using a high-speed disperser with a rotation speed of 800 to 1200 r / min to obtain a slurry.

8. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: In step S3, the process conditions used for ball milling are: the diameter of the zirconia ball is 1.5-2.5 mm, the ball-to-material ratio is (2.8-3.2):1, the ball milling temperature is 35-42°C, the ball milling speed is 40-60 r / min, and the ball milling time is 5-10 h.

9. The method for preparing micron-sized flaky silver powder for HJT solar cells according to claim 1, characterized in that: In step S3, separation is to separate the ball-milled slurry and the zirconium oxide balls by a sieve to obtain slurry A, and wash the zirconium oxide balls to obtain slurry B; slurry A and slurry B are combined and then filtered under reduced pressure to obtain flaky silver powder; Washing is to use deionized water to wash the flaky silver powder until the conductivity is ≤20μS / cm; The drying is carried out at 50℃~80℃ for 8h~24h; the sieving is carried out using a 200-mesh screen.

10. Micron-sized flaky silver powder for HJT solar cells prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silver powder and manufacturing method thereof

    CN102133635A

  • Preparation method of flake silver powder with low burning loss

    CN102248176A

  • Manufacturing method for conductive silver powder used for touch screen UV-type laser engraving silver paste

    CN105081343A

  • Silver powder, preparation method of silver powder and laser etching silver paste

    CN111438369A

  • Micron-sized spherical silver powder as well as preparation method and application thereof

    CN112589113A